Modelling the relationship between Building Information Modelling (BIM) implementation barriers, usage and awareness on building project lifecycle - Olanrewaju, O.I. (Elsevier Ltd, 2022)
The concept of a successful building project should be implemented across the project's lifecycle phases to obtain maximum profits without compromising the standard. Although BIM implementation in developing countries is limited, much research has focused on BIM drivers. However, there is less evidence to thoroughly investigate the influence of BIM barriers and awareness on the project lifecycle. This study addresses barriers to BIM implementation in building projects in developing countries. It investigates the influence of BIM barriers on awareness of BIM during the project lifecycle. Thus, a comprehensive literature review is required to build a conceptual model. Subsequently, the Partial Least Square Structural Equation Modelling (PLS-SEM) was developed using a questionnaire survey tool. Data were collected from 90 building experts in Nigeria. The model's outputs highlighted that cost and standards, process and economic, technology and business, and training and people are the most critical barriers to BIM implementation that should be avoided. Furthermore, the model prediction revealed that eliminating BIM barriers has a minor impact on sufficient knowledge throughout the building project lifecycle. The findings provide the basis for policy making in developing countries concerning the successful completion of projects by avoiding BIM barriers; it will likewise enhance the success of building projects through BIM. Â© 2021 Elsevier Ltd